(untitled) (Andamios, Revista de Investigación Social, 2025)
This article proposes that the youth of Legua Emergencia one of the most stigmatised neighbourhoods in Chile. Confront violence and territorial stigma through public artistic performances. Such expressions seek to recreate a sense of community and identity in order to confront the social impact of drug trafficking and territorial stigma on the lives of their neighbours. Through the ethnographic study of a ‘batucada’, it is argued that their performances in the neighbourhood constitute forms of subjectivation and politicization for young people based on the affective experiences they have in public space, although they may be overlooked by normative sociological approaches based on deliberative and rational models. The performances of the ‘batucada’ contest the meaning of stigmatising representations and defend the identity of Legua Emergencia before the wider political community.